Analisis Uji Kesesuaian Pesawat Sinar X Radiografi Mobile Merk ALLENGERS Type MARS-6 SBM - Nani Lasiyah; Yeni Pertiwi; Romi Mulyadi; Nofri Anto (Universitas Indraprasta PGRI Jakarta, 2022)
The advances in technology experience significant developments anually, especially in the medical devices in the form of mobile x ray. The use of mobile x-ray radiation in the field of radiodiagnostics for various medical purposes needs to pay attention to two aspects, namely the risks and benefits. Therefore, the radiation protection is needed to reduce the damaging effects of radiation caused by radiation exposure. To ensure the accuracy and safety in the use of X-ray radiation, calibration procedures or conformity tests are carried out periodically. This study performs a conformity test on a mobile general radiography machine ALLENGERS, type MARS-6 SBM, with serial number 2162 used to examine the patients. The results of the conformity test using the Collimator Test and coin markers, mobile X-ray were declared to have passed the test as seen in the results from measurements using a Lux Meter, namely 101 Lux, with the score of a coin marker collimator of 3%.